Investigation of Angular Spectrum of Scattered Inert Gas Ions from the InGaP (001) Surface - Karimov, M.K.; Kutliev, U.O.; Bobojonova, S.B.; Otabaeva, K.U. (Physics and Chemistry of Solid State, 2021)
It has been shown that this method is quite suitable for surface studies and diagnostics of many component materials. The values of the azimuthal angle of distribution of Ne, Ar and Xe ions scattered from InGaP (001) <110> are obtained. The relationship between the spatial variables of the scattered beam (mainly azimuthal angular spectra) and the type of ions has been established. The correlation between focusing properties of surface semichannel with a type of bombardment ion at the different angle of incidence has been shown.